2018
DOI: 10.4103/jips.jips_302_17
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude about relining of complete dentures in clinical practice: A cross-sectional study

Abstract: Awareness and scientific knowledge about the relining materials and procedure should be enhanced within general dental practitioners through CDE program and workshops. Steps should be taken to include relining procedure as a part of undergraduate clinical curriculum as well as internship program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
1
6
0
1
Order By: Relevance
“…Regarding the response to the preparation performed before relining, majority of respondents removed all calculus and slimy layer with ultrasonic cleaner, and disinfected the denture before relining. Similar results were obtained in a study conducted by Rathi A et al [24]. About frequently of replacing the relining materials, 46.3% of respondents thought that replacement of relining material should be done after 6 months.…”
Section: Figure-2|duration Of Use Of Soft Liners (N=82)supporting
confidence: 88%
See 2 more Smart Citations
“…Regarding the response to the preparation performed before relining, majority of respondents removed all calculus and slimy layer with ultrasonic cleaner, and disinfected the denture before relining. Similar results were obtained in a study conducted by Rathi A et al [24]. About frequently of replacing the relining materials, 46.3% of respondents thought that replacement of relining material should be done after 6 months.…”
Section: Figure-2|duration Of Use Of Soft Liners (N=82)supporting
confidence: 88%
“…Majority of the participants knew that relining is the process used to resurface the tissue side of the denture. However, in a similar study it was revealed that about 26% were not sure about the exact procedure of relining [24]. Majority 90.2% of the respondents felt that relining improves stability and retention of the denture.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the present case, the upper denture fabricated within the RM approach with no border molding showed a poor retention. Thus, a relining procedure with all functional probes can be performed in analog workflow either directly or indirectly [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Após a acrilização das próteses e no momento da instalação da overlay há a necessidade de reembasamento. A finalidade do procedimento é melhorar a estabilidade e retenção 22 . Essa etapa pode ser realizada de forma direta (reembasamento imediato) ou de forma indireta (reembasamento mediato), em que se molda o paciente com a prótese em posição e o reembasamento é confeccionado no laboratório 23 .…”
Section: Discussionunclassified